Prognostic impact of early tumor shrinkage and depth of response in patients with microsatellite instability-high metastatic colorectal cancer receiving immune checkpoint inhibitors. Issue 4 (13th April 2021) - Fucà, Giovanni; Corti, Francesca; Ambrosini, Margherita; Intini, Rossana; Salati, Massimiliano; Fenocchio, Elisabetta; Manca, Paolo; Manai, Chiara; Daniel, Francesca; Raimondi, Alessandra; Morano, Federica; Corallo, Salvatore; et al.
Abstract : Background: Immune checkpoint inhibitors (ICIs) are the new standard of care in microsatellite instability-high (MSI-H)/deficient mismatch repair (dMMR) metastatic colorectal cancer (mCRC). Since tumor response dynamic parameters already shown a strong association with survival outcomes in patients with mCRC treated with first-line therapy, we investigated the association of early tumor shrinkage (ETS) and depth of response (DoR) in patients with MSI-H/dMMR mCRC treated with ICIs. Methods: This is a retrospective, multicenter, cohort study in patients with dMMR and/or MSI-high mCRC treated with ICIs (anti-PD-1/PD-L1 with or without anti-CTLA-4 agents) with measurable disease and at least one post-baseline radiological disease reassessment. The Kaplan-Meier method and Cox proportional-hazards regression models were used for survival analyses. A maximally selected statistics method in a Cox regression model for progression-free survival (PFS) was used to determine the optimal cut-offs for ETS and DoR. Results: We included a total of 169 patients: 116 (68.6%) were treated with anti-PD-1 monotherapy, whereas 53 (31.4%) with anti-PD-1 plus anti-CTLA-4 agents. Patients with primary progressive disease (N=37, 21.9%), experienced an extremely poor overall survival (OS) and were evaluated separately. In patients with clinical benefit, we observed a significant association between ETS and DoR with both OS and PFS, and we identified a relative reduction of at least 1% as the optimal cut-off for ETS and a relative reduction of at least 50% as the optimal cut-off for DoR. Conclusions: ETS and DoR are important prognostic factors in patients with MSI-high mCRC treated with ICIs that might be useful to design treatment intensification/deintensification strategies. A prospective validation of both is warranted.